2021
DOI: 10.3390/ijerph18126229
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Maternal and Paternal Parenting Styles Scale in Chilean Adolescents

Abstract: Parenting style has been related to a series of positive outcomes that extend into adulthood. The aim of this study was to analyze the psychometric properties of the maternal and paternal parenting styles scale (PSS-MP) in a sample of adolescents. A cross-sectional design was used, with a probability sample of 2683 adolescents (48.8% women) from 32 public, private, and subsidized schools in Chile. In total, four confirmatory factor models were contrasted, which was the best fit to support the originally propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Furthermore, these results are in line with those reported by Álvarez-García et al [ 50 ], who created the abbreviated version of the parenting styles scale. With respect to the reliability indices, the results, in general, show satisfactory values for each factor; these results are in line with previous studies [ 28 , 50 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, these results are in line with those reported by Álvarez-García et al [ 50 ], who created the abbreviated version of the parenting styles scale. With respect to the reliability indices, the results, in general, show satisfactory values for each factor; these results are in line with previous studies [ 28 , 50 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, the theoretical proposal behind the scale used in this research provides a more complex understanding and evaluation of parenting styles [ 28 , 29 ]. Thirdly, this instrument constitutes a contribution to studies in this area due to its ease of administration, encompassing various dimensions that refer to different characteristics of the interaction between parents and their adolescent children in a single instrument, which is psychometrically robust [ 28 , 29 , 50 , 52 ]. Therefore, this scale can be useful in intervention processes, allowing for comparisons to be made between the initial situation and possible changes at the end.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the scales that assess parenting styles were designed and validated in European countries or in the United States (Rajan et al, 2020) and only a few were validated in Latin America. In this respect, the Maternal and Paternal Parenting Styles Scale (PSS-MP), consisting of six factors, was validated in Chilean population (Gálvez et al, 2021). Likewise, in Peru, a study reported the convergent validity of the Maternal Behavior Q-Sort (MBQS), which comprises three factors and 90 questions (Bárrig-Jó et al, 2020).…”
Section: Discussionmentioning
confidence: 99%